Marginal loss surplus redistribution through Aumann-Shapley joint transmission loss cost allocation in electricity markets - Cleto, Saliw Campos
Marginal Loss Surplus (MLS) in a Locational Marginal Price (LMP)-designed electricity market is a consequence of allocating the non-linear losses to market participants based on their marginal loss contribution. Though small in value relative to congestion surplus, MLS merits detailed analysis since it is substantial enough to cause dispute among market stakeholders. Game Theory?s Aumann-Shapley Joint Cost Allocation method (AS) is utilized in this study to separate the transmission loss and redistribute MLS among market participants. This method employs loss sensitivities calculated from the Distributed Slack Bus with Angle Reference Transposed load flow formulation (DSBARTF) to eliminate the arbitrariness of the solution to the choice of slack bus and to reflect actual system operation.